2006
DOI: 10.1016/j.jcf.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The genetic background of osteoporosis in cystic fibrosis: Association analysis with polymorphic markers in four candidate genes

Abstract: There was no evidence that the genes under study, with the possible exception of ESR1 gene variants, may modulate bone phenotype in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Furthermore, a functional study on the codon 447 SNP showed that there was no statistically significant difference between the proline 447 and leucine 447 variants with respect to their calcitonin-binding characteristics or their abilities to signal when stimulated with calcitonin [39]. The other SNP in the CALCR gene region, IMS-JST054515 (C/T, intron 3), has been suggested as a genomic marker for severe periodontitis in Japanese patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a functional study on the codon 447 SNP showed that there was no statistically significant difference between the proline 447 and leucine 447 variants with respect to their calcitonin-binding characteristics or their abilities to signal when stimulated with calcitonin [39]. The other SNP in the CALCR gene region, IMS-JST054515 (C/T, intron 3), has been suggested as a genomic marker for severe periodontitis in Japanese patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…13 However, people with CF continue to have a reduced life expectancy and a significant burden of disease management, and many develop symptoms of other diseases, such as diabetes and osteoporosis, at a younger age than normal. [14][15][16][17] In recent years, there has been an effort to find drugs and treatments that target the cause of CF rather than its symptoms. Several groups have discovered small molecules that enhance F508del CFTR trafficking to the membrane (correctors) or increase its opening probability (potentiators), [18][19][20][21][22][23][24][25][26][27][28][29] and some of these have advanced to clinical trials to evaluate their safety and efficacy for treating CF.…”
Section: Introductionmentioning
confidence: 99%
“…However, this fact has not resulted in quality of life because different comorbidities have been observed in adulthood. Disturbances in bone metabolism, particularly significant reductions in bone mineral density (BMD), are recognized as additional and serious complications in these CF patients, with prevalence ranging from 40% to 70% 2 , 3 . The low BMD found in these patients is multifactorial and many factors have been suggested as explanation 4 - 10 .…”
Section: Introductionmentioning
confidence: 99%